A música erudita na conformação de espaços na cidade: Belo Horizonte de 1925 a 1950 - Myrian Ribeiro Aubin (2015)
This study aims to identify the insertion of classical music in Belo Horizonte during the years from 1925 to 1950 through cultural practices that happened through social institutions and the State. The starting point is the first music social and teaching institution made official by the state government, the Conservatório Mineiro de Música. From this point, other social institutions and communication media are approached, such as Symphony Societies, Radio and Press, responsible for forming and revealing the musicians as well as these classical music presentations in the city. For the groups associated to the classical music, this would be conformer of spaces responsible for changing Belo Horizonte into a modern city and with a specific project of civilization defined by certain notions of culture and education. From the selected documentation, the places where the classical music was present in the city were mapped. To understand the reach of the practices connected to the classical music the material concerning the pianists as fundamental agents for the process of inserting the classical music in the city was selected. Finally, the commercial practices turned to the classical music focused on the piano as another space for music instituted in Belo Horizonte were analyzed. It searched the dialog, during the presentation and configuration of the spaces that the classical music was conforming in the city, the material collected at the newspaper sources with the ideals of modernity and civilization defended by those connected to it. Therefore, the identification of these spaces created by and for the classical music were essential in spreading an image of Minas Gerais capital as modern and civilized city.